Problematyka warunku co do przyszłości w świetle rotalnego wyroku c. McKay z dnia 14 maja 2012 r. - Dzierżon, Ginter (Ius Matrimoniale, 2016)
The presented article is a commentary on the rotal sentence c. McKay of 14 May 2012. What attracted the author’s attention is the question of the condition concerning the future added to the marital contract. As the author stated in the introduction, the commentary did not appear as a result of a new doctrinal or procedural solution introduced in the legal order or in the actual form of the sentence. The main reason for writing it was the fact that in the course of the case a new question appeared which was not previously discussed in rotal jurisdiction and was connected with the plaintiff’s intention to make use of new procreational techniques such as heterological insemination and surrogate maternity. In the course of the discussed case, mentioning such events from the marital life of the parties did not bring the result awaited by the plaintiff, i.e. the annulment of marriage. The panel of judges based their argumentation on the fact that the subject of the condition was not precisely specified by the plaintiff while the main counter-argument against adding the condition to the marital contract was the long-lasting married life of the parties.